Methacholine induced headache. Issue 3 (March 1995) - Carratala, C; Gea, J G; Aguar, M C; Grau, S; Espadaler-Medina, J M; Broquetas, J M
Abstract : A lung function technician developed episodes of headache, probably related to the use of methacholine. The headache disappeared with breathing 100% oxygen. Cholinergic agents are known to induce headaches but the mechanism remains unclear. Vascular factors could be implicated.